The labor market from a spatial perspective (2013)
This article shows the findings of a systematic literature review which aims to analyze labor market from a spatial perspective. The results suggest that the greatest theoretical and empirical developments are focused on spatial distribution of economic activity and consequently on occupational profiles, and the spatial mismatch hypothesis. Nevertheless, the greater development of the spatial techniques has allowed expanding the analysis to other problems of the labor market.